Effects of Two Different Exogenous Surfactant Preparations on Serial Peripheral Perfusion Index and Tissue Carbon Monoxide Measurements in Preterm Infants with Severe Respiratory Distress Syndrome - Demet Terek; Deniz Gonulal; Ozge Altun Koroglu; Mehmet Yalaz; Mete Akisu; Nilgun Kultursay (Pediatrics and Neonatology, 2015)
Administration of an exogenous surfactant may affect both ventilatory and hemodynamic parameters in preterm infants with respiratory distress syndrome (RDS). Peripheral perfusion may be expected to be influenced, and serial perfusion index (PI) values may show this effect. Noninvasive transcutaneous carbon monoxide (TCO) monitoring may show RDS severity, oxidative and inflammatory stress, and response to surfactant treatment. Methods: This randomized controlled nonblinded study was performed in 30 preterm infants with RDS, treated with poractant alfa (n = 15) or beractant (n = 15); 18 preterm infants without RDS served as a control group. Oxygenation and hemodynamic parameters were recorded and compared through the first 6 hours of treatment. PI and TCO values were measured prior to (Tp), immediately after (T0), and at 5 minutes (T5), 30 minutes (T30), 60 minutes (T60), and 360 minutes (T360) after the bolus surfactant administration. The mean arterial pressure, oxygenation index, pH, and lactate levels were recorded simultaneously. Results: Both study groups had lower Tp PI and higher Tp TCO levels than controls. Both surfactant preparations improved the PI, TCO, mean arterial pressure, oxygenation index, pH, and lactate levels at the end point of T360. However, the median Tp PI value of 1.3 first decreased to 0.86 at T0 (P < 0.001), and then it increased to 0.99 at T5 (p < 0.001) and to 1.25 at T30 (p = 0.037). The median Tp TCO value of 3 decreased to 2, 1.5, 0, and 0 at T0, T5, T30, and T60, respectively (p < 0.001). PI more quickly recovered to Tp values (30 minutes vs. 60 minutes) and reached the control group values (30 minutes vs. 360 minutes) with beractant compared to that with poractant alfa. TCO recovered to Tp values in both groups at the same time (5 minutes vs. 5 minutes), but reached the control group values more quickly (5 minutes vs. 30 minutes) with poractant alfa than with beractant. Conclusion: Patients with RDS had poor perfusion, and PI improved with both surfactant preparations only following a short decline in the 1st minute. The expected improvement of PI occurred earlier in the beractant subgroup. TCO declined in both groups, showing lung improvement and decreased oxidative/inflammatory stress, and it was normalized earlier with poractant alfa.